Neurologic Deep Dive: A Simulation Case of Diagnosing and Treating Decompression Sickness for Emergency Medicine Residents - Xiao C. Zhang; Antoinette Golden; David S. Bullard (Association of American Medical Colleges, 2016)
Abstract Introduction Decompression sickness (DCS) is a rare and dangerous complication from a rapid decrease in environmental pressure, commonly seen in patients leaving a compressed-air environment, such as scuba divers, aviators, and deep tunnel workers. Failure to clinically diagnose and adequately treat DCS with hydration and supplemental oxygen before bridging to hyperbaric oxygen (HBO) therapy can result in permanent residual symptoms or, in rare cases, death. Despite the increasing incidence of DCS, there are limited published simulation case studies discussing this perilous environmental exposure. Methods This fictional simulation case is written for emergency medicine residents to diagnose and manage DCS from a live-actor patient presenting with unilateral neurologic symptoms and concealed cyanotic mottling (cutis marmorata). This case ran for four separate iterations at a simulation center, with a resident, fellow, and attending acting as specific confederates for their respective roles. Following each case, the learners were debriefed at bedside, discussed a PowerPoint presentation, and underwent a question-and-answer session. Results Based on postsimulation qualitative assessments, junior and senior residents correctly identified DCS, but junior residents alone were less likely to elicit pertinent social history or to fully physically examine the patient without the presence of senior residents. Both resident groups were able to verbally explain the fundamental DCS pathophysiology to the patient, but junior residents were unable to specifically direct oxygenation, hydration, and HBO protocols for DCS. After case completion and debriefing, all learners demonstrated achievement of primary learning objectives. Discussion Overall, we noted this case worked well for junior EM residents with senior-resident backup. Both learner groups appreciated the concealed elements of case, including scuba diving history and exposed dermatologic findings, and reported that these were invaluable learning moments for all future patient encounters, not just those limited to DCS.